2020
DOI: 10.1109/access.2020.2985089
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT: Impersonation Attack Detection via Edge Computing Using Deep Autoencoder and Feature Abstraction

Abstract: An ever-increasing number of computing devices interconnected through wireless networks encapsulated in the cyber-physical-social systems and a significant amount of sensitive network data transmitted among them have raised security and privacy concerns. Intrusion detection system (IDS) is known as an effective defence mechanism and most recently machine learning (ML) methods are used for its development. However, Internet of Things (IoT) devices often have limited computational resources such as limited energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 13 publications
0
49
0
Order By: Relevance
“…However, supervised learning alone is not feasible for modern IDSs because there are many possible attacks with different features, which renders the training process computationally expensive and time consuming. Therefore, most recent research works have applied autoencoders in IDSs and obtained promising outputs [48,49]. An autoencoder is an unsupervised learning technique that uses neural networks for the so-called task of representation learning [50].…”
Section: System Modelmentioning
confidence: 99%
“…However, supervised learning alone is not feasible for modern IDSs because there are many possible attacks with different features, which renders the training process computationally expensive and time consuming. Therefore, most recent research works have applied autoencoders in IDSs and obtained promising outputs [48,49]. An autoencoder is an unsupervised learning technique that uses neural networks for the so-called task of representation learning [50].…”
Section: System Modelmentioning
confidence: 99%
“…In the second work, several shallow algorithms such as random forest are also used to detect anomalies using the output of VAE. In a similar manner, the work introduced in [20] employs VAE with gradientbased linear SVM to detect some particular attacks on the AWID2019 dataset, where SVM first reduces feature dimension then VAE selects the most relevant features. It is reported that the detection rate is higher than state-of-art models.…”
Section: Autoencoder (Ae)mentioning
confidence: 99%
“…It is reported that the detection rate is higher than state-of-art models. In addition to models in [18][19][20], the model introduced in [21] combines VAE with GAN and DNN. Basically, it uses VAE to obtain new input representations formed in a statistical and nonlinear way then GAN to make less-represented intrusions augmented.…”
Section: Autoencoder (Ae)mentioning
confidence: 99%
“…They built the classifier for normal and impersonation attack samples. A quite similar approach was followed by Lee et al that emphasized three phases in the proposed IDS, feature extraction using SAE, feature selection using Mutual Information and C4.8, and SVM based classification with gradient descent optimization [14]. The goal was to reduce the number of features as much as possible for classification.…”
Section: Related Workmentioning
confidence: 99%